Prevalencia de ancilostomiasis canina en la ciudad de Arenillas en el año 2010 - García Romero, Andrea Patricia (2011)
The next investigation is about Canine Ancylostomiasis , it was made in Arenillas and , it was based on the next objectives: 1) establish the prevalence of the Canine Ancylostomiasis according to age,gender and origin .2) determine the degree of parasitic infection. The methodology in the work area consisted in divide the zones to take feces samples of 246 animals to be analyzed in the laboratory to determine the variables. The results are: 1.- Prevalence of Canine Ancylostomiasis, 2.- Prevalence de Canine Ancylostomiasis because of the age, 3.- Canine Ancylostomiasis because of the animal gender, 4.-Prevalence of Canine Ancylostomiasis for origin and 4.- the number of canine ancylostomiasis eggs according to their origin. After the respective analysis and tabulation of data, it resulted that the prevalence of canine ancylostomiasis, In 246 evaluated only 118 animals tested were found to be positive with the presence of this disease giving an infection percentage of 47.97%. According to their age, the largest number of animals tested with this disease accounted for less than a year dog. In all assessed areas, animals have the presence of this disease, whith value ranges from 28 to 34 positive dogs, with a percentage ranging from 41,93 to 54.83%. It was concluded that the animals tested to determine the prevalence of canine ancylostomiasis Arenillas found to be lower than those found by Moscoso (2000) but higher than the Apollo (2007) in their investigations in the city of Machala.